Complement Fixation Reaction for the Diagnosis of Type II Avian (Marek's) Leukosis - Hamdy, Farouk (1970)
The present study was designed to find a complement fixation (CF) reaction for the diagnosis of type II lymphoid leukosis, to learn some of the characteristics of the CF antigen, and to investigate the development of CF antibody response to this infection. JM virus-specific antigen was demonstrated in tumorous chicken tissue, in JM virus-infected chick embryo material, in JM virus-infected chicken kidney, and in duck embryo fibroblast tissue culture by using JM virus-immune rabbit serum. This CF antigen did not show cross-reactivity with Rous sarcoma virus or with RIF-type viruses. It was partially heat-labile. The CF activity was restored at —70 C for 10 months and was resistant to intermittent freeze-thaw treatment. The CF antigen may be denatured by ethyl alcohol, but no significant deleterious effects were noted after ether or chloroform treatment. JM virus-specific CF antibody could not be demonstrated by the direct complement dilution method or by the indirect or inhibition form of the CF test in infected or immunized chicken sera.